Kenaf based cement bonded particleboard: a preliminary study on mechanical and physical properties / Mohamad Jani Saad …[et al.] - Saad, Mohamad Jani; Sudin, Rahim; Salleh, Jalali; Idzwan, Shahril; Fazimie, Muhammad (2006)
The construction of cement board that using kenafs' fibres as Ihe main filler in the cement boards has been developed and their performances in terms of mechanical and physical properties are evaluated. Kenaf based cement bonded particleboard (CBP) at four (4) different of kenaf cement ration which are starling from 1:2.5, 1:5, 1:2.75 and 1:3 have been produced and their mechanical and physical properties were evaluated and the Malaysian Standard is used as standard requirement. Two types of kenaf parts which are bast and core fibers are used with fiber size fixed at 2mm film during board making in purposes to study the performance of board based on different fiber types. The treatment on the fiber during mixing with cement also undergoes which using ammonium sulphate and aluminum suphate. From the earlier results it shows an indicalor that bast long fiber contributed better result of mechanical testing than core short fiber of cement board, but both of them produced nearly same figure of thickness swelling test results and they pass the minimum number of standard requirement for thickness swelling. Meanwhile, fiber that contained of aluminum sulphate show the promising yield than the ammonium sulphates ' samples in terms of mechanical ada physical tests results and exceeded the minimum standard level.